¬¬¬¬¬¬¬¬TINJAUAN YURIDIS TINDAK PIDANA PENIPUAN DENGAN MENGGUNAKAN HIPNOTIS (DI WILAYAH HUKUM KEPOLISIAN RESORT KOTA SAMARINDA) - Denny Tri Wibowo (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
AbstractionForm of crime in the big city at present is more diverse. For a long time criminal uses violence or take advantage on people can be note in the last couple years appeared a unique form, it is fraudulence use hypnosis. This method works only by tapped the shoulder of the victim or glared to him. The crime with hypnosis modus is not only issue alone but happening around us. The most victim is women, in split second the victim without conscious obey all the command from villain, usually the villain will ask for the victim to give all their treasure, such as jewelry, money or even submit their virginity also.  Criminal offense with using hypnosis knowledge is one of the kind modus of crime this time happening rife in the society. The crime with hypnosis modus widely used caused the method to trick the victim is not need violence. For that with the increasing number of violations of the law, then the law must be enforced. So through law enforcement is expected to reduce crime in the community.These researched to elaborated the view of criminal law against the crime of using hypnosis in the Resort City Police Samarinda included the role and efforts of law enforcement officers to solve the issued. These researched had done in  the Resort City Police Samarinda. The method used for these researched were using primary legal material, tertiary and secondary data to supported the implementation to the problems examined.The result of this researched showed the rules of law enforcement officers especially Police has a very important rules to solved the crimes in a country, law enforcer as a represent of country to nurturing, protect and guide of the society. In  this researched view of criminal law against the crime of using hypnosis was committed the crime of fraud using hypnosis could be imprisoned with article 378 KUHP with a maximum sanction of criminal penalties for four years imprisonment. Meanwhile the effort of law enforcer to overcome crime criminal fraud by using hypnosis in Samarinda are (1) prevention by doing extension activities and increase security surveillance in various places.(2) enforcement effort are prosecution and punishment for the fraudulent and development effort by penitentiary be in the form of spiritual founding, physical founding and skills founding.